Detection by multiplex PCR of Mycoplasma species associated with dairy cattle in Argentina = Detección por PCR multiplex de especies de Mycoplasma asociadas a ganado lechero en Argentina - Neder, Veronica Elizabeth; Amadio, Ariel; Calvinho, Luis Fernando (Elsevier, 2021)
There is scarce information about the frequency and epidemiological and clinical features associated with the presence of Mycoplasma spp. in Argentine dairy herds. The objectives of this study were to develop a multiplex PCR for identifying M. bovis and M. canadense and to describe the frequency of Mycoplasma spp. isolated from clinical samples submitted to a diagnostic laboratory. Of a total of 1548 samples from intramammary infections, bulk tank milk and biological fluids, 38 Mycoplasma isolates were obtained. M. bovis, M. canadense, M. californicum and M. leachii were detected by using two multiplex PCRs, confirming their presence in clinical conditions in dairy cattle. The techniques used in the present study can be useful to broaden the knowledge about Mycoplasma infections in cattle, since the search for these organisms is not usually included in routine diagnoses.